Phase shifting white light interferometry using colour CCD for optical metrology and bio-imaging applications - Upputuri, Paul Kumar (2018)
Phase shifting white light interferometry (PSWLI) has been widely used for optical metrology applications because of their precision, reliability, and versatility. White light interferometry using monochrome CCD makes the measurement process slow for metrology applications. WLI integrated with Red-Green-Blue (RGB) CCD camera is finding imaging applications in the fields optical metrology and bio-imaging. Wavelength dependent refractive index profiles of biological samples were computed from colour white light interferograms. In recent years, whole-filed refractive index profiles of red blood cells (RBCs), onion skin, fish cornea, etc. were measured from RGB interferograms. In this paper, we discuss the bio-imaging applications of colour CCD based white light interferometry. The approach makes the measurement faster, easier, cost-effective, and even dynamic by using single fringe analysis methods, for industrial applications.